Method for evaluating abrasion resistance of rubber composition and rubber composition
Patent Information
- Application Number
- JP2024065529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-02
- Filing Date
- 2024-04-15
- Publication Date
- 2025-02-14
AI Technical Summary
【0008】 本発明は、X線散乱測定又は中性子散乱測定によってゴム組成物の耐摩耗性を評価する方法であって、前記(式1)で表されるqの領域において、X線散乱測定又は中性子散乱測定を実施することにより得られる散乱強度曲線I(q)に対し、前記(式2)でカーブフィッティングして得られる質量フラクタル次元Dに基いてゴム組成物の耐摩耗性を評価する方法であるので、ゴム組成物の耐摩耗性を高精度に評価できる。すなわち、実車による耐摩耗性能の評価手法がタイヤを作製して走行テストを実施する必要があり、時間的、コスト的にも不利である一方、本発明の方法では、ゴム試験片(ゴム組成物)を作製してX線又は中性子を照射するという簡便な手法により、短時間かつ低コストで、精度よく耐摩耗性を評価することが可能である。
Smart Images

Figure 2025022734000022 
Figure 2025022734000001 
Figure 2025022734000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for evaluating the abrasion resistance of a rubber composition and to a rubber composition. [Background technology]
[0002] Conventionally, a method for evaluating the wear resistance of tires has been known in which vulcanized rubber for wear tests is prepared using the same compounding as the tire tread rubber, and this vulcanized rubber is subjected to wear using an indoor wear tester such as a Lambourn abrasion tester to evaluate the wear resistance (see Patent Document 1).
[0003] However, in the conventional method, the properties of the vulcanized rubber for the abrasion test and the tread rubber of the tire to be evaluated may differ due to differences in vulcanization conditions, etc. For this reason, there is a problem that the results of abrasion resistance predicted by the conventional evaluation method do not match the results of abrasion resistance when the tire to be evaluated is actually mounted on a vehicle and driven. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-308447 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to solve the above problems and to provide a method for evaluating the abrasion resistance of a rubber composition with high accuracy. [Means for solving the problem]
[0006] The inventors have conducted studies and found that the mass fractal dimension D, which is obtained by curve fitting a scattering intensity curve obtained by performing X-ray scattering measurement or neutron scattering measurement in a specific region with a specific equation, shows a high correlation with the wear resistance of a rubber composition, and that the smaller the mass fractal dimension D, the better the wear resistance tends to be. This is presumably because not allowing the filler network to develop excessively (i.e., a smaller mass fractal dimension) increases the number of micro sacrificial fracture sites, suppressing macro fracture (i.e., wear) and improving wear resistance.
[0007] That is, the present invention provides a method for evaluating the abrasion resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement, In the region q represented by the following formula 1, the scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement is (q) The present invention relates to a method for evaluating the abrasion resistance of a rubber composition based on a mass fractal dimension D obtained by curve fitting using the following (Equation 2).
number
number
[0008] The present invention relates to a method for evaluating the abrasion resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement, and the method includes: (q)In contrast, since the method evaluates the abrasion resistance of a rubber composition based on the mass fractal dimension D obtained by curve fitting using the above-mentioned (Equation 2), the abrasion resistance of the rubber composition can be evaluated with high accuracy. That is, while the method for evaluating abrasion resistance using an actual vehicle requires the preparation of a tire and carrying out a running test, which is disadvantageous in terms of time and cost, the method of the present invention makes it possible to evaluate abrasion resistance with high accuracy in a short time and at low cost by the simple method of preparing a rubber test piece (rubber composition) and irradiating it with X-rays or neutrons. [Brief description of the drawings]
[0009] [Figure 1] An example of a scattering intensity curve and fitting results obtained by SANS measurement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention relates to a method for evaluating the abrasion resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement, and the method includes: (q) In contrast, this is a method for evaluating the abrasion resistance of a rubber composition based on the mass fractal dimension D obtained by curve fitting using the above (Equation 2).
[0011] In the above method, the X-ray scattering measurement can be suitably performed by SAXS (Small-Angle X-ray Scattering (scattering angle: usually 10 degrees or less)) measurement, in which a rubber composition is irradiated with X-rays and the scattering intensity is measured. In small-angle X-ray scattering, X-rays are irradiated onto a substance, and among the X-rays scattered, those with small scattering angles are measured to obtain structural information of the substance, and regular structures at the level of several nanometers, such as the microphase separation structure of a polymer material, can be analyzed.
[0012] To obtain detailed molecular structure information from SAXS measurements, it is desirable to measure X-ray scattering profiles with a high S / N ratio. For this purpose, the X-rays emitted from the synchrotron must be at least 1010 (photons / s / mrad 2 / mm 2 It is preferable that the luminance of the synchrotron is equal to or higher than 0.1% bw, where bw indicates the bandwidth of the X-rays emitted from the synchrotron. Examples of such synchrotrons include beamlines BL03XU and BL20XU of the large-scale synchrotron radiation facility SPring-8 owned by the Japan Synchrotron Radiation Research Institute.
[0013] The above X-ray brightness (photons / s / mrad 2 / mm 2 / 0.1%bw) is preferably 10 10 More than 10, more preferably 12 Although there is no particular upper limit, it is preferable to use an X-ray intensity that is not greater than the level at which radiation damage occurs.
[0014] The photon count (photons / s) of the X-rays is preferably 10 7 More than 10, more preferably 9 Although there is no particular upper limit, it is preferable to use an X-ray intensity that is not greater than the level at which radiation damage occurs.
[0015] In the above method, the neutron scattering measurement can be suitably performed by SANS (Small-Angle Neutron Scattering (scattering angle: usually 10 degrees or less)) measurement, in which a rubber composition is irradiated with neutrons and the scattering intensity is measured. In small-angle neutron scattering, a substance is irradiated with neutrons and neutrons scattered with small scattering angles are measured to obtain structural information of the substance, and regular structures at the level of several nanometers, such as the microphase separation structure of a polymer material, can be analyzed.
[0016] In the SANS measurement, a method using a known magnetic structure or a deuteration method can be used. When the deuteration method is adopted, for example, a polymeric material is swollen with a deuterated solvent, and the polymeric material in equilibrium in the deuterium solvent is irradiated with a neutron beam to measure the scattering intensity. Here, examples of the deuterated solvent for swelling the polymeric material include deuterium water, deuterated hexane, deuterated toluene, deuterated chloroform, deuterated methanol, deuterated DMSO ((D3C)2S=O), deuterated tetrahydrofuran, deuterated acetonitrile, deuterated dichloromethane, deuterated benzene, and deuterated N,N-dimethylformamide.
[0017] The neutron beam used in neutron scattering measurements such as SANS can be obtained using beamline SANS-J at the JRR-3 research reactor owned by the Japan Atomic Energy Agency.
[0018] Similar to the SAXS measurement, the neutron flux intensity (neutrons / cm) of the above neutron beam is selected because it provides a neutron scattering profile with a high signal-to-noise ratio. 2 / s) is preferably 10 3 More than 10, more preferably 4 Although there is no particular upper limit, it is preferable to use a neutron flux intensity that is not greater than the level at which radiation damage occurs.
[0019] In the above method, the X-ray and neutron scattering measurements are carried out in the region q represented by the following formula 1: q (nm -1 ) region, the larger the value, the more detailed information on the molecular structure can be obtained. Therefore, X-ray and neutron scattering measurements are performed in the region where q is 10 nm -1 The following areas are preferred: 5×10 -2 nm -1 The following areas are preferred: 2×10 -3 nm -1 5×10 or more -3 nm -1 The following areas are particularly preferred:
number
[0020] In the SAXS measurement, the scattered X-rays are detected by an X-ray detection device, and an image is generated by an image processing device or the like using the X-ray detection data from the X-ray detection device.
[0021] Examples of X-ray detection devices that can be used include two-dimensional detectors (X-ray film, nuclear emulsion plates, X-ray imaging tubes, X-ray fluorescence intensifiers, X-ray image intensifiers, X-ray imaging plates, X-ray CCDs, X-ray amorphous bodies, etc.) and line sensor one-dimensional detectors. An appropriate X-ray detection device can be selected depending on the type and state of the polymeric material to be analyzed.
[0022] As the image processing device, one that can generate a normal X-ray scattering image based on X-ray detection data from an X-ray detection device can be appropriately used.
[0023] SANS measurement can be performed based on the same principle as SAXS measurement, where scattered neutron beams are detected by a neutron beam detector, and an image is generated by an image processing device or the like using neutron beam detection data from the neutron beam detector. As described above, the neutron beam detector may be a known two-dimensional or one-dimensional detector, and the image processing device may be one capable of generating a known neutron beam scattering image, and may be selected appropriately.
[0024] Then, the rubber composition is subjected to measurements such as SAXS measurement and SANS measurement, and the obtained scattering intensity curve is analyzed by the following method, whereby the mass fractal dimension D can be obtained.
[0025] As shown in Figure 1, the scattering intensity curve I obtained by SAXS and SANS measurements (q) Then, curve fitting is performed using the following (Equation 2), and the mass fractal dimension D, which is a fitting parameter, can be found by the least squares method.
number
[0026] The mass fractal dimension D obtained by fitting is estimated to be derived from, for example, in the case of a rubber composition containing, in its molecular structure, at least one reinforcing agent such as carbon black or silica, and / or an inorganic filler represented by the general formula mM xSiOy zH2O (wherein M is at least one selected from the group consisting of metals selected from the group consisting of aluminum, magnesium, titanium, calcium, and zirconium, oxides and hydroxides of these metals, hydrates thereof, and carbonates of these metals, and m, x, y, and z are constants).
[0027] As described above, the correlation between the mass fractal dimension D and wear resistance is high, and the smaller the value of D, the better the wear resistance. In particular, a rubber composition having D of less than 2.30 can be said to have excellent wear resistance. The value of D is preferably 2.25 or less, more preferably 2.20 or less, even more preferably 2.17 or less, even more preferably 2.15 or less, and even more preferably 2.12 or less. Meanwhile, the lower limit of the value of D is 1.00, since in principle 1≦D≦3.
[0028] Here, in the present invention, the mass fractal dimension D means the degree of packing of a substance in a unit volume, and in a filler-filled rubber composition, it is the degree of packing of the filler (filling agent) in a unit volume, that is, it is estimated to be the degree of development of the filler network.
[0029] It is believed that not overdeveloping the filler network (i.e., having a smaller mass fractal dimension D) increases the number of microscopic sacrificial fracture sites, thereby suppressing macroscopic fracture (i.e., wear).
[0030] The mass fractal dimension D can be adjusted by the types and amounts of chemicals such as rubber components, fillers, and silane coupling agents blended into the rubber composition. The mass fractal dimension D can be reduced by changing the silica dispersibility depending on the type of silane coupling agent. Specifically, the mass fractal dimension D can be reduced by using a modified rubber as the rubber component, as described below, reducing the amount of the modified rubber, and using a mercapto-based silane coupling agent as the silane coupling agent.
[0031] As the rubber composition (rubber material) to be applied to the method of the present invention, for example, one containing a rubber component and a filler is suitably used.
[0032] The weight average molecular weight of the rubber component usable in the above rubber composition is preferably 50,000 or more, more preferably 150,000 or more, even more preferably 200,000 or more, and particularly preferably 270,000 or more, and is preferably 2,000,000 or less, more preferably 1,500,000 or less, and even more preferably 1,000,000 or less.
[0033] In this specification, the weight average molecular weight (Mw) and number average molecular weight (Mn) can be determined by standard polystyrene conversion based on the measured values obtained by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M manufactured by Tosoh Corporation).
[0034] The rubber component usable in the rubber composition may be either unmodified or modified rubber, but modified rubber is preferred from the viewpoint of reducing the mass fractal dimension D of the rubber composition. The modified rubber may be a rubber having a functional group that interacts with a filler such as silica. For example, the modified rubber may be a terminal modified rubber (terminal modified rubber having the functional group at the terminal) in which at least one terminal of the rubber is modified with a compound (modifier) having the functional group, a main chain modified rubber having the functional group at the main chain, a main chain terminal modified rubber having the functional group at the main chain and terminal (for example, a main chain terminal modified rubber having the functional group at the main chain and at least one terminal modified with the modifier), or a terminal modified rubber modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or an epoxy group introduced therein.
[0035] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), and an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms) are preferred.
[0036] Specific examples of rubber components that can be used in the rubber composition include diene rubbers. Examples of diene rubbers include isoprene rubbers, butadiene rubbers (BR), styrene butadiene rubbers (SBR), styrene isoprene butadiene rubbers (SIBR), ethylene propylene diene rubbers (EPDM), chloroprene rubbers (CR), and acrylonitrile butadiene rubbers (NBR). Examples of rubber components include butyl rubbers and fluororubbers. These may be used alone or in combination of two or more. These rubber components may be modified or hydrogenated, and extended rubbers extended with oils, resins, liquid rubber components, and the like may be used. Among these, from the viewpoint of reducing the mass fractal dimension D of the rubber composition, the rubber composition preferably includes a diene rubber, more preferably includes at least one selected from the group consisting of isoprene rubbers, BR, and SBR, more preferably includes SBR, and even more preferably includes BR and SBR.
[0037] As the modified rubber, specifically, there is a compound described in JP-A-2010-116554, which is a compound represented by the following general formula: [ka] (In the formula, R 1 and R 2 is hydrogen, [ka] or [ka] and at least R 1 and R 2 Either of these is not hydrogen. 3 represents hydrogen or a hydrocarbon group having 1 to 4 carbon atoms. X is (CR 8 R 9 ) l , (CR 10 R 11 ) m -NR12 -(CR 13 R 14 ) n , (CR 10 R 11 ) m -O-(CR 13 R 14 ) n , or (CR 10 R 11 ) m -S-(CR 13 R 14 ) n X represents a saturated ring-forming moiety consisting of [ka] or [ka] Z may be substituted with (CR 8 R 9 ) l , (CR 10 R 11 ) m -NR 12 -(CR 13 R 14 ) n , (CR 10 R 11 ) m -O-(CR 13 R 14 ) n , or (CR 10 R 11 ) m -S-(CR 13 R 14 ) n R represents a saturated ring-forming moiety consisting of 4 ~R 7 R represents hydrogen, an aliphatic hydrocarbon group having 1 to 30 carbon atoms, an alicyclic hydrocarbon group having 3 to 30 carbon atoms, an aromatic hydrocarbon group having 5 to 30 carbon atoms, or a heterocyclic group having 3 to 30 ring atoms. 4 ~R 7 may be the same or different. R 0 and R 8 ~R 14R represents hydrogen, an aliphatic hydrocarbon group having 1 to 30 carbon atoms, an alicyclic hydrocarbon group having 3 to 30 carbon atoms, or an aromatic hydrocarbon group having 5 to 30 carbon atoms. 0 and R 8 ~R 14 may be the same or different. l represents an integer of 3 to 10. m and n represent integers of 1 to 9. and a polymer having at least one end modified with a modifying agent having a functional group containing at least one atom selected from nitrogen, oxygen and silicon.
[0038] When the rubber composition contains an isoprene-based rubber, the content of the isoprene-based rubber is preferably 5 mass% or more, more preferably 10 mass% or more, and preferably 30 mass% or less, more preferably 20 mass% or less, based on 100 mass% of the rubber component.
[0039] When the rubber composition contains BR, the content of BR is, from the viewpoint of reducing the mass fractal dimension D of the rubber composition, preferably 5 mass% or more, more preferably 15 mass% or more, even more preferably 20 mass% or more, and still more preferably 30 mass% or more, and is preferably 60 mass% or less, more preferably 40 mass% or less, based on 100 mass% of the rubber component.
[0040] When the rubber composition contains SBR, the content of SBR is, from the viewpoint of reducing the mass fractal dimension D of the rubber composition, preferably 40 mass% or more, more preferably 60 mass% or more, and preferably 95 mass% or less, more preferably 85 mass% or less, even more preferably 80 mass% or less, and still more preferably 70 mass% or less, based on 100 mass% of the rubber component.
[0041] Examples of fillers that can be used in the rubber composition include carbon atom-based fillers, inorganic fillers, etc. Examples of carbon atom-based fillers that can be used include carbon black, etc. Examples of inorganic fillers that can be used include silica, metal salts of sulfate, silicon carbide, and compounds represented by the following formula: mM xSiOy zH2O (In the formula, M is at least one metal selected from the group consisting of Al, Mg, Ti, Ca and Zr, or an oxide or hydroxide of the metal, m is an integer of 1 to 5, x is an integer of 0 to 10, y is an integer of 2 to 5, and z is an integer of 0 to 10.) Examples of the compound represented by the above formula include alumina, alumina hydrate, aluminum hydroxide, magnesium hydroxide, talc, titanium white, titanium black, calcium oxide, calcium hydroxide, aluminum calcium oxide, clay, pyrophyllite, bentonite, aluminum silicate, calcium silicate, aluminum calcium silicate, magnesium silicate, zirconium, and zirconium oxide.
[0042] These fillers may be used alone or in combination of two or more. Among these, the rubber composition preferably contains carbon black and / or silica, and more preferably contains silica.
[0043] The carbon black is not particularly limited, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shinnikka Carbon Co., Ltd., Columbia Carbon Co., Ltd., and the like. These may be used alone or in combination of two or more.
[0044] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 75 m 2 / g or more, more preferably 95m 2 / g or more, and preferably 120m 2 / g or less, more preferably 100m 2 Within the above range, there is a tendency for the effect to be better obtained. The N2SA of carbon black is a value measured in accordance with JIS K6217-2:2001.
[0045] When the rubber composition contains carbon black, the content of carbon black is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and preferably 20 parts by mass or less, more preferably 10 parts by mass or less, per 100 parts by mass of the rubber component, from the viewpoint of reducing the mass fractal dimension D of the rubber composition.
[0046] Examples of silica include dry silica (anhydrous silicic acid) and wet silica (hydrated silicic acid), but wet silica is preferred because it has a large number of silanol groups. Commercially available products include those from Evonik Degussa, Tosoh Silica, Solvay Japan, and Tokuyama. These may be used alone or in combination of two or more.
[0047] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 100m 2 / g or more, and preferably 250m 2 / g or less, more preferably 220m 2 Within the above range, there is a tendency for the effect to be better obtained. The N2SA of silica is a value measured by the BET method in accordance with ASTM D3037-81.
[0048] When the rubber composition contains silica, the content of silica is preferably 30 parts by mass or more, more preferably 60 parts by mass or more, and preferably 120 parts by mass or less, more preferably 100 parts by mass or less, per 100 parts by mass of the rubber component, from the viewpoint of reducing the mass fractal dimension D of the rubber composition.
[0049] In the above rubber composition, the content of the filler (the total amount of carbon atom-based fillers such as carbon black, and inorganic fillers such as silica, metal salts of sulfate, silicon carbide, and the compound represented by the above formula) is preferably 30 parts by mass or more, more preferably 60 parts by mass or more, and is preferably 120 parts by mass or less, more preferably 100 parts by mass or less, per 100 parts by mass of the rubber component.
[0050] When the rubber composition contains silica, it is preferable that the rubber composition further contains a silane coupling agent. The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, and bis(4-trimethoxysilylbutyl)trisulfide. , bis(3-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N , N-dimethylthiocarbamoyl tetrasulfide, 3-triethoxysilylpropyl methacrylate monosulfide, and other sulfide-based agents; mercapto-based agents such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and Momentive's NXT and NXT-Z; vinyl-based agents such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based agents such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy-based agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Among these, mercapto-based silane coupling agents are preferred from the viewpoint of reducing the mass fractal dimension D of the rubber composition. Commercially available products include those from EVONIK, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industry, Azumax, and Dow Corning Toray Co., Ltd. These may be used alone or in combination of two or more.
[0051] The content of the silane coupling agent is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more, per 100 parts by mass of the silica content, and is preferably 10 parts by mass or less, and more preferably 7 parts by mass or less.
[0052] The rubber composition may contain sulfur. Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, and the like, which are commonly used in the rubber industry.
[0053] In the rubber composition, the amount of sulfur is preferably 1.0 part by mass or more, more preferably 1.3 parts by mass or more, based on 100 parts by mass of the rubber component. The amount is preferably 7.0 parts by mass or less, more preferably 5.0 parts by mass or less.
[0054] The rubber composition may contain a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolylguanidine, and orthotolylbiguanidine. These may be used alone or in combination of two or more.
[0055] In the rubber composition, the content of the vulcanization accelerator is preferably 0.5 parts by mass or more, more preferably 1.0 part by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 8.0 parts by mass or less, more preferably 6.0 parts by mass or less.
[0056] The rubber composition may contain other compounding agents such as a plasticizer (oil, liquid polymer, resin, etc.), an antioxidant, stearic acid, zinc oxide, wax, and a mold release agent.
[0057] The rubber composition (rubber material) can be produced, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll or a Banbury mixer, followed by vulcanization.
[0058] Known conditions can be used as appropriate for the kneading conditions. For example, in the base kneading process in which additives other than the vulcanizing agent (crosslinking agent) and the vulcanization accelerator are kneaded, the kneading temperature is preferably 100° C. or higher, more preferably 120° C. or higher, and also preferably 180° C. or lower, more preferably 170° C. or lower. In the finish kneading process in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is preferably 80° C. or higher, and also preferably 120° C. or lower, more preferably 110° C. or lower. In addition, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is preferably 140° C. or higher, more preferably 150° C. or higher, and also preferably 190° C. or lower, more preferably 185° C. or lower.
[0059] Since the method of the present invention can evaluate the abrasion resistance with high accuracy, it can be suitably used for evaluating the abrasion resistance of tire components such as treads. When manufacturing a pneumatic tire using the above rubber composition, the rubber composition is extruded in an unvulcanized state to match the shape of a tread or the like, molded in a tire building machine by a normal method, and bonded together with other tire components to form an unvulcanized tire (raw tire), which is then heated and pressurized in a vulcanizer. EXAMPLES
[0060] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.
[0061] The various chemicals used in the synthesis of the monomer (1) and the polymers (1) to (3) will be collectively described below. Cyclohexane: Kanto Chemical Co., Ltd. Pyrrolidine: Kanto Chemical Co., Ltd. Divinylbenzene: Sigma-Aldrich 1.6M n-butyllithium hexane solution: Kanto Chemical Co., Ltd. Isopropanol: Kanto Chemical Co., Ltd. Styrene: Kanto Chemical Co., Ltd. Butadiene: Takachiho Chemical Industry Co., Ltd. Tetramethylethylenediamine: Kanto Chemical Co., Ltd. Modifier: 3-(N,N-dimethylaminopropyl)trimethoxysilane manufactured by Azmax Corporation 2,6-tert-Butyl-p-cresol: manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Methanol: Kanto Chemical Co., Ltd.
[0062] (Synthesis of Monomer (1)) In a 100 ml container that had been thoroughly purged with nitrogen, 50 ml of cyclohexane, 4.1 ml of pyrrolidine, and 8.9 ml of divinylbenzene were added, and 0.7 ml of a 1.6 M n-butyllithium hexane solution was added at 0° C. and stirred. After 1 hour, isopropanol was added to terminate the reaction, and the monomer (1) was obtained by extraction and purification.
[0063] (Synthesis of polymer (1)) In a 1000 ml pressure vessel that had been thoroughly purged with nitrogen, 600 ml of cyclohexane, 12.6 ml of styrene, 71.0 ml of butadiene, 0.06 g of monomer (1), and 0.11 ml of tetramethylethylenediamine were added, and 0.2 ml of 1.6 M n-butyllithium hexane solution was added at 40°C and stirred. After 3 hours, 0.5 ml of modifier was added and stirred. After 1 hour, 3 ml of isopropanol was added to terminate the polymerization. After adding 1 g of 2,6-tert-butyl-p-cresol to the reaction solution, the mixture was reprecipitated with methanol and dried by heating to obtain polymer (1).
[0064] (Synthesis of polymer (2)) Polymer (2) was obtained in the same manner as in the above-mentioned polymer (1) except that 0.17 g of monomer (1) was used.
[0065] (Synthesis of polymer (3)) Polymer (3) was obtained in the same manner as in the above-mentioned polymer (1) except that 0.29 g of monomer (1) was used.
[0066] The various chemicals used in each formulation are summarized below. BR: BR150B manufactured by Ube Industries, Ltd. Polymers (1) to (3): Synthesized by the above method Silica: EVONIK Ultrasil VN3 (N2SA: 175m 2 / g) Silane coupling agent 1: Evonik Degussa Si69 Silane coupling agent 2: NXT-Z45 manufactured by Momentive Oil: Diana Process AH-24 manufactured by Idemitsu Kosan Co., Ltd. Stearic acid: NOF Corporation's "Tsubaki" stearic acid Anti-aging agent: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Wax: Sunnock wax manufactured by Ouchi Shinko Chemical Co., Ltd. Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Vulcanization accelerator 1: Noccela CZ (N-cyclohexyl-2-benzothiazolyl sulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator 2: Noccelaer D (N,N'-diphenylguanidine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0067] [Method for evaluating the abrasion resistance of a rubber composition] According to the composition shown in Table 1, materials other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer. Next, sulfur and vulcanization accelerator were added, and the mixture was kneaded for 3 minutes at about 80°C using an open roll to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was press-vulcanized for 12 minutes at 170°C to obtain a vulcanized rubber composition.
[0068] The obtained unvulcanized rubber composition was extruded into a tread shape using an extruder equipped with a predetermined shaped die, and then laminated together with other tire components to form an unvulcanized tire. The tire was press-vulcanized at 170°C for 12 minutes to produce a test tire (tire size: 195 / 65R15).
[0069] The vulcanized rubber composition and the test tire obtained above were subjected to the following evaluations. The results are shown in Table 1.
[0070] 1.SAXS measurement method A sheet-shaped sample (the above vulcanized rubber composition) with a thickness of about 1 mm that had been swollen in toluene for 12 hours was attached to a sample holder, and the area of q (area of q: 2×10 -3 ~5×10 -3 nm -1 ) at room temperature. The scattering intensity curves obtained from measurements at BL03XU and BL20XU were combined using the least squares method. The two curves were combined by fixing the scattering intensity curve obtained from BL03XU on the wide-angle side and shifting the scattering intensity curve obtained from BL20XU on the small-angle side, resulting in scattering intensity curve I from SAXS measurement. (q) The obtained scattering intensity curve I (q)Curve fitting was performed using the above (Equation 2), and the mass fractal dimension D, which is a fitting parameter, was found by the least squares method.
[0071] (SAXS device) SAXS: SAXS measurement equipment attached to beamlines BL03XU and BL20XU of the large-scale synchrotron radiation facility SPring-8 owned by the Japan Synchrotron Radiation Research Institute (Measurement conditions) X-ray brightness: 5×10 12 photons / s / mrad 2 / mm 2 / 0.1%bw X-ray photon count: 2×10 9 Photons / s X-ray energy: 8 keV (BL03XU), 23 keV (BL20XU) Distance from sample to detector: 3m (BL03XU), 160m (BL20XU) (Detector) 2D detector (imaging intensifier and CCD camera)
[0072] 2. Actual vehicle testing The above test tires were mounted on a domestically produced FF vehicle, and the tire tread depth was measured after 8,000 km of driving. The distance traveled when the tire groove depth was reduced by 1 mm was calculated and indexed using the following formula. The higher the index, the better the wear resistance. (Distance traveled when tire tread of each compound is reduced by 1 mm) / (Distance traveled when tire tread of compound 1 is reduced by 1 mm) x 100
[0073] [Table 1]
[0074] From Table 1, it can be seen that there is a high correlation between the mass fractal dimension D and the wear resistance, and the smaller D is, the better the wear resistance is.
[0075] [Rubber composition] According to the composition shown in Table 2, materials other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer. Next, sulfur and vulcanization accelerator were added, and the mixture was kneaded for 3 minutes at about 80°C using an open roll to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was press-vulcanized for 12 minutes at 170°C to obtain a vulcanized rubber composition.
[0076] The obtained unvulcanized rubber composition was extruded into a tread shape using an extruder equipped with a predetermined shaped die, and then laminated together with other tire components to form an unvulcanized tire. The tire was press-vulcanized at 170°C for 12 minutes to produce a test tire (tire size: 195 / 65R15).
[0077] The vulcanized rubber composition and the test tire obtained above were subjected to the following evaluations. The results are shown in Table 2.
[0078] 1.SAXS measurement method A sheet-shaped sample (the above vulcanized rubber composition) with a thickness of about 1 mm that had been swollen in toluene for 12 hours was attached to a sample holder, and the area of q (area of q: 2×10 -3 ~5×10 -3 nm -1 ) at room temperature. The scattering intensity curves obtained from measurements at BL03XU and BL20XU were combined using the least squares method. The two curves were combined by fixing the scattering intensity curve obtained from BL03XU on the wide-angle side and shifting the scattering intensity curve obtained from BL20XU on the small-angle side, resulting in scattering intensity curve I from SAXS measurement. (q) The obtained scattering intensity curve I (q) Curve fitting was performed using the above (Equation 2), and the mass fractal dimension D, which is a fitting parameter, was found by the least squares method.
[0079] (SAXS device) SAXS: SAXS measurement equipment attached to beamlines BL03XU and BL20XU of the large-scale synchrotron radiation facility SPring-8 owned by the Japan Synchrotron Radiation Research Institute (Measurement conditions) X-ray brightness: 5×10 12 photons / s / mrad 2 / mm 2 / 0.1%bw X-ray photon count: 2×10 9 Photons / s X-ray energy: 8 keV (BL03XU), 23 keV (BL20XU) Distance from sample to detector: 3m (BL03XU), 160m (BL20XU) (Detector) 2D detector (imaging intensifier and CCD camera)
[0080] 2. Actual vehicle testing The above test tires were mounted on a domestically produced FF vehicle, and the tire tread depth was measured after 8,000 km of driving. The distance traveled when the tire groove depth was reduced by 1 mm was calculated and indexed using the following formula. The higher the index, the better the wear resistance. (Distance traveled when tire tread of each compound is reduced by 1 mm) / (Distance traveled when tire tread of compound 16 is reduced by 1 mm) x 100
[0081] [Table 2]
[0082] The present invention (1) is a method for evaluating the abrasion resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement, In the region q represented by the following formula 1, the scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement is (q) In contrast, this is a method for evaluating the abrasion resistance of a rubber composition based on the mass fractal dimension D obtained by curve fitting using the following (Equation 2).
number
number
[0083] In the present invention (2), the range of q is 2×10 -3 ~5×10 -3 nm -1 This is a method for evaluating the abrasion resistance of the rubber composition according to the present invention (1).
[0084] The present invention (3) is a method for evaluating the abrasion resistance of the rubber composition according to the present invention (1) or (2), which contains a diene rubber and a filler.
[0085] The present invention (4) is a method for evaluating the abrasion resistance of a rubber composition in any combination with any of the present inventions (1) to (3) which is a rubber composition for tires.
[0086] The present invention (5) provides a scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement in a region q represented by the following (Equation 1): (q) In contrast, the rubber composition has a mass fractal dimension D of less than 2.30, which is obtained by curve fitting using the following formula (2).
number
number
[0087] The present invention (6) is the rubber composition according to the present invention (5), in which the mass fractal dimension D is 2.20 or less.
[0088] The present invention (7) is the rubber composition according to the present invention (5), in which the mass fractal dimension D is 2.15 or less.
[0089] In the present invention (8), the range of q is 2×10 -3 ~5×10 -3 nm -1and any of the rubber compositions according to the present invention (5) to (7).
[0090] The present invention (9) is a rubber composition comprising a rubber component containing a diene rubber and any of the present inventions (5) to (8) containing a filler in any combination.
[0091] The present invention (10) is the rubber composition according to the present invention (9), wherein the diene rubber contains a styrene-butadiene rubber, and the content of the styrene-butadiene rubber is 40 to 80 mass % in 100 mass % of the rubber component.
[0092] The present invention (11) is the rubber composition according to the present invention (9) or (10), further comprising a mercapto-based silane coupling agent.
[0093] The present invention (12) is a rubber composition for tires, which is an arbitrary combination with any of the present inventions (5) to (11).
Claims
1. A method for evaluating the abrasion resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement, comprising: In the region q represented by the following formula 1, a scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement is (q) A method for evaluating the abrasion resistance of a rubber composition based on a mass fractal dimension D obtained by curve fitting using the following (Equation 2): [0010] [0025]
2. The area of q is 2×10 -3 ~5×10 -3 nm -1 The method for evaluating the abrasion resistance of a rubber composition according to claim 1,
3. 2. The method for evaluating the abrasion resistance of a rubber composition according to claim 1, wherein the rubber composition comprises a diene rubber and a filler.
4. The method for evaluating the abrasion resistance of a rubber composition according to claim 1, wherein the rubber composition is a rubber composition for tires.
5. In the region q represented by the following formula 1, a scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement is (q) A rubber composition having a mass fractal dimension D of less than 2.30, which is obtained by curve fitting using the following formula (2): [0030] [0045]
6. The rubber composition according to claim 5, wherein the mass fractal dimension D is 2.20 or less.
7. The rubber composition according to claim 5, wherein the mass fractal dimension D is 2.15 or less.
8. The area of q is 2×10 -3 ~5×10 -3 nm -1 The rubber composition according to claim 5 .
9. The rubber composition according to claim 5, comprising a rubber component containing a diene rubber and a filler.
10. The rubber composition according to claim 9, wherein the diene rubber comprises a styrene-butadiene rubber, and the content of the styrene-butadiene rubber is 40 to 80 mass % in 100 mass % of the rubber component.
11. The rubber composition according to claim 9, further comprising a mercapto-based silane coupling agent.
12. The rubber composition according to claim 5, which is a rubber composition for tires.
Citation Information
Patent Citations
Tire abrasion lifetime prediction method
JP2005308447A